PENGARUH MEDIA SANDPAPER LETTER TERHADAP KEMAMPUAN MENGENAL HURUF SISWA DI SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Suci Riani; Ismail Saleh Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted to determine the effect of sandpaper letters on students’ ability to recognise letters at the Kampung Bharu Malaysia learning centre. The study was conducted in a Year 1 class with eight students. Based on the results of the study, the average pre-test score was 20 and the post-test score was 44.25. This shows a significant increase in students’ letter recognition skills. In the t-test, the sig value obtained was 0.000 < 0.05, meaning that there is an effect of sandpaper letters on students’ letter recognition skills at the Kampung Bharu Malaysia learning centre.